The growth of reading literacy through the BAGJA stage at Batu Merah Ambon State SLB - Isna Rizqiyya (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2022)
This study aims to find out how the BAGJA stages can grow reading literacy in SLB Negeri Batu Merah Ambon. This research is a qualitative case study research that takes the object of research at the Batu State Special School in Ambon. The research sample consisted of school principals, fellow teachers, education staff, and students at the level SMPLB and SMALB levels. The technique in this study uses observation, interviews, and documentation. The results of this study indicate that the BAGJA stage can grow students' reading literacy in the school environment, especially in SLB Negeri Batu Merah Ambon. The school has a very comfortable library made for a place for students to read. The school library has a variety of interesting books for students to read, as well as a library room complete with air conditioning. Thus, the students of the level SMPLB and SMALB levels often visit the school library on Fridays and Saturdays from the daily schedule that has been made by the school.